Erotismo, mística e morte: a tríade adeliana (Eroticism, mysticism and death in Adélia Prado poetry) - DOI: 10.5752/P.2175-5841.2012v10n25p104 - Oliveira, Cleide Maria de (Horizonte, 2012)
The article aims to present the main themes of the poetry of Adelia Prado, a writer who since the first book (Bagagem, 1976) to the last (A duração do dia, 2010) has surprised audiences and critics with the articulation of issues that common sense believes divorced, more properly, a mystical religiosity and a burning eroticism. Thinking about the erotic and the mystical in Adelia Prado´s poetry means thinking about human being as circumscribed by the horizon of death, knowing that more than a simple theme, these are elements of a structured and sustained poetry that is rooted in a extreme corporeality that assumes body and language as always open to the sacred. However, although religious, his poetry is neither naive nor catechetical. Such mystical experience, similar to what happens with the great mystics Santa Tereza de Avilla and São João da Cruz, takes place in the body, which becomes the gateway to the mystery.